PENEGAKAN HUKUM TERHADAP TINDAK PIDANA EKSPLOITASI SEKSUAL ANAK DI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Mardiansyah Saputra; Emilda Firdaus; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Kids are creatures of God Almighty and social beings. Since the child in the womb has a right to life and independence as well as better protection of parents, family, community, nation and state. It is quite alarming trend is the proliferation of sexual crimes not only affects women, but also affects children under the age. These girls as objects commodity (trading) or depraved gratification (animalistic) of a person and a particular group of sexual conduct business in order to gain economic double. These girls as objects commodity (trading) or depraved gratification (animalistic) of a person and a particular group of sexual conduct business in order to gain economic double.This research is a sociological research that want to see the unity between law and society with the gap between fennel and das sein sollen. This research was conducted in the jurisdiction of Police Resort Kota Pekanbaru, while the sample population is a whole party related to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this research through interviews and review of the literature.From the results of research can be concluded, first, law enforcement, preventive (prevention) and repression (repression). Second, barriers faced by internal factors are the obstacles include factors of quantity and quality of personnel and funds are limited to the operational process of investigation and investigations. While his external factors, among others, under the age-old victim is usually difficult to communicate in terms of providing information on the actions to happen to him, usually a mentally retarded child that it is difficult in terms of member information, as well as the perpetrators fled (DPO). The lack of public participation would be legal awareness. Third, efforts to overcome the barriers that fix the internal deficiencies is to improve the quantity and quality of personnel Pekanbaru City Police Resort and act effectively and efficiently manage available funds. The inadequacies of the external of children who have suffered the sexual exploitation was accompanied by a child psychologist from the Riau Police, children who have mental retardation accompanied by a teacher Special School for police in taking account of the victim, the perpetrator fled or escaped, police Resort Pekanbaru city in this case to provide information or share data information kepolsek offender, police station, as well as improving legal awareness and legal complianceKeywords: Law Enforcement - Crime - Sexual Exploitation of Children